Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5194/aab-61-475-2018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of some Turkish sheep breeds based on the sequencing of the <i>Ovar-DRB1</i> gene in the major histocompatibility complex (MHC) gene region

Abstract: In this research, Ovar-DRB1 gene in the major histocompatibility complex (MHC) gene region was surveyed by DNA sequencing in some of the native sheep breeds that are reared in Turkey. A total of 80 samples were collected from eight different Turkish native sheep breeds, and these samples were used for DNA sequencing.The exon 2 region of Ovar-DRB1 in the MHC gene region was polymerase chain reaction (PCR) amplified and sequenced. A total of 25 new alleles were revealed in the Ovar-DRB1 gene in Turkish native sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Different restriction sites in DNA represent the genetic divergence between different populations or related species within a population. Özdil et al ( 2018 ) demonstrated genetic diversity among 11 donkey species in Turkey by conducting PCR-RFLP of two genes. The restriction sites of DraII, MboI, and EagI on the lactoferrin gene (LTF) and PstI on the κ-casein gene (CSN3) have been validated to identify the polymorphism among the donkey population (Özdil et al 2018 ).…”
Section: Techniques For Identification and Genetic Conservation Of Sp...mentioning
confidence: 99%
See 2 more Smart Citations
“…Different restriction sites in DNA represent the genetic divergence between different populations or related species within a population. Özdil et al ( 2018 ) demonstrated genetic diversity among 11 donkey species in Turkey by conducting PCR-RFLP of two genes. The restriction sites of DraII, MboI, and EagI on the lactoferrin gene (LTF) and PstI on the κ-casein gene (CSN3) have been validated to identify the polymorphism among the donkey population (Özdil et al 2018 ).…”
Section: Techniques For Identification and Genetic Conservation Of Sp...mentioning
confidence: 99%
“…Özdil et al ( 2018 ) demonstrated genetic diversity among 11 donkey species in Turkey by conducting PCR-RFLP of two genes. The restriction sites of DraII, MboI, and EagI on the lactoferrin gene (LTF) and PstI on the κ-casein gene (CSN3) have been validated to identify the polymorphism among the donkey population (Özdil et al 2018 ). Meikasari et al ( 2019 ) have also made elucidation of low genetic diversity among the seahorse ( Hippocampus comes ) found in Bintan waters.…”
Section: Techniques For Identification and Genetic Conservation Of Sp...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, the genetic diversity of native sheep breeds reared in Turkey and Algeria has been investigated [ 6 , 7 ]. These studies aimed to explore the impact of polymorphisms in the MHC gene region, which has the potential to influence future animal breeding strategies.…”
Section: Introductionmentioning
confidence: 99%